CYBER CRIME DAN PENERAPAN CYBER LAW DALAM PEMBERANTASAN CYBER LAW DI INDONESIA - Lita Sari Marita (Universitas Bina Sarana Informatika, 2015)
Using of internet connection is not a new things nowday, every one can acces internet whereever, whenever, anytime anywhere they need or want. Is not dificult to find hotspot area, so nothing more can’s stop people to knowing and connecting with other people in all country.Considering of using internet causing negatif affcet, such as cyber cryme, when there is a cybercrime then we know we need cyber law.to knowing what is cyber crime and what is cybercrime this is a explaination to be known.This paper made for us to know deeply about cyber crime and cyber law, consist of definition, sample and conclution, hoply with reading this people may understanding what is cyber crime and cyber law.Keyword : internet, cybercrime, cyber law